(3QhVI GdWGdHjf hYeOI GdeJbjfs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3GdQGaYj , CHh GdbGSe YHO GdcQje Hf eMeO Hf YHO GdcQje GdQGaYj GdbRhjfj, GdQGaYj GdbRhjfj,J (B623 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf GdETJZGd HGdYde ef CaVd GdbQH hCLd GdWGYGJ hCge CfhGY GdNjQ s
(3BNQgG (B:s
(3ef GdRhGFO GdegeGJ hGdfhGOQ BNQ GdcJGH s
(3GdfSNI HgG MhGTs
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3Gdabg GdTGaYjs